Pelaksanaan Projek Penguatan Profil Pelajar Pancasila dalam Membentuk Karakter Disiplin Siswa - Dwi Dinda Framudia; Syarnubi; Rohmadi; Irja Putra Pratama; Aristophan Firdaus (PAI RAFAH, 2024)
The independent curriculum is a curriculum that refers to and leads to the development of students' talents and interests This study aims to determine what the implementation of the Pancasila Student Profile Strengthening Project is like in shaping the disciplinary character of grade 7 students at SMPN 2 OKU and to find out the supporting and inhibiting factors regarding the implementation of the Pancasila student profile strengthening project in shaping the disciplinary character of grade 7 students at SMPN 2 OKU. This research uses descriptive qualitative research methods. The subjects of this study were the principal, vice principal for curriculum, P5 coordinator teacher, teaching teacher and students of class VII.3. The data collection techniques used were observation, interview, and documentation. Data analysis techniques through data reduction, data presentation, and conclusion drawing. Based on the results of research and data analysis, it can be concluded that the implementation of the project to strengthen the profile of Pancasila students (P5) in shaping the disciplinary character of grade 7 students at SMPN 2 OKU is carried out with 3 stages, namely planning, implementation, and evaluation. Through determining the time allocation, forming a team of facilitators, choosing a common theme, selecting projects, and designing project modules. The theme and project chosen was Wake up the soul and body. The inhibiting factors faced are sourced from students, and the facilitator teacher himself